Pemikiran Pendidikan Islam Perspektif KH. M. Hasyim Asyâ€™ari - Mukani, Mukani (J-PAI: Jurnal Pendidikan Agama Islam, 2014)
Education thought of KH. M. Hasyim Asyâ€™ari is the concept of characterÂ education, but also consistently gives positive contribution to the IndonesiaÂ civilization. Its dedication not only focuses on one field, but also onÂ education, politic, social, religion, physical confrontation, organization,Â and the other intellectual works. Not only to educate young generationÂ through Tebuireng Pesantren that was built, but for next generation, KH.Â M. Hasyim Asyâ€™ari has inherited many books or holy books that able asÂ main reference to search alternative solution of various problems thatfaced by nation. KH. M. Hasyim Asyâ€™ari has been given fundamentalÂ conceptual framework for national education. Technical and operationalÂ steps must still be reviewed to implement the educational thinking.Â Figure of NUâ€™s founding at some point want to do the balancing forÂ education in Indonesia. Not only formality aspects, but also substanceof the meaning of education must be internalized and implemented inÂ the life of students. In the end, Indonesia education is expected able toÂ produce â€œproductâ€ that not only have cognitive intelligence (smart), butÂ also have good virtue.keywords: Contribution, Struggle, Character Education, KH. M. HasyimAsyâ€™ari